Fabrication of sintered calcium carbonate parts with multiscale porosity: producing artificial rocks for petrophysical studies and other applications - Morais, Mateus Mota (2024)
Petroleum engineering uses natural rock samples (core plugs) in several applications, including calibrating characterization tools, studying enhanced oil recovery, and developing and validating numerical models. However, natural carbonate core plugs are extremely heterogeneous and can be limited in number due to cost and legal usage restrictions. Therefore, it is difficult to obtain reproducible and comparable experimental results using them, especially when destructive experiments are involved. A possible solution is producing carbonate rock replicas with controlled porosity and permeability. However, two main challenges stand out: 1) consolidating calcium carbonate without causing its thermal decomposition and 2) producing the multiscale pore structure. In this thesis, the first challenge was overcome by sintering the calcite using a carbon dioxide atmosphere to avoid its calcination (Chapter 3). Concerning the second challenge, the multiscale porosity was achieved with two different solutions. The first was the compaction of carbonate powder with pore formers, resulting in calcite core plugs with controlled porosity and pore size (Chapter 4). The samples presented up to 93% relative density and mechanical properties similar to natural rocks (compressive strength up to 110 MPa). The second strategy was additive manufacturing (vat-photopolymerization) to produce the macroscopic features combined with pore formers to adjust the micrometric porosity (Chapters 5 to 7). The 3D-printed calcite samples presented an excellent geometrical resolution (channels > 600 μm), moderate porosity (41-48 %), moderate mechanical properties (flexural strength up to 9 MPa), and permeability similar to natural rocks (30-50 mD). The first method is suited for larger samples with high mechanical strength, such as core plugs for petrophysical tests. The second is indicated for thin-walled carbonate structures with complex geometries, such as microfluidic models, artificial corals, bone scaffolds, and sea animal skeleton replicas. This thesis presents an innovative manufacturing process for calcium carbonate parts with multiscale porosity. It is the first work demonstrating the production of artificial rocks based on pure calcite with sufficient strength to withstand petrophysical tests at high pressures.